Pro-angiogenic effect of RANTES-loaded polysaccharide-based microparticles for a mouse ischemia therapy. Issue 1 (December 2017) - Suffee, N.; Visage, C.; Hlawaty, H.; Aid-Launais, R.; Vanneaux, V.; Larghero, J.; Haddad, O.; Oudar, O.; Charnaux, N.; Sutton, A.
Abstract Peripheral arterial disease results from the chronic obstruction of arteries leading to critical hindlimb ischemia. The aim was to develop a new therapeutic strategy of revascularization by using biodegradable and biocompatible polysaccharides-based microparticles (MP) to treat the mouse hindlimb ischemia. For this purpose, we deliver the pro-angiogenic chemokine Regulated upon Activation, Normal T-cell Expressed and Secreted (RANTES)/CCL5 in the mouse ischemic hindlimb, in solution or incorporated into polysaccharide-based microparticles. We demonstrate that RANTES-loaded microparticles improve the clinical score, induce the revascularization and the muscle regeneration in injured mice limb. To decipher the mechanisms underlying RANTES effectsin vivo, we demonstrate that RANTES increases the spreading, the migration of human endothelial progenitor cells (EPC) and the formation of vascular network. The main receptors of RANTESi .e . CCR5, syndecan-4 and CD44 expressed at endothelial progenitor cell surface are involved in RANTES-inducedin vitro biological effects on EPC. By using two RANTES mutants, [E66A]-RANTES with impaired ability to oligomerize, and [44 AANA47 ]-RANTES mutated in the main RANTES-glycosaminoglycan binding site, we demonstrate that both chemokine oligomerization and binding site to glycosaminoglycans are essential for RANTES-induced angiogenesisin vitro . Herein we improved the muscle regeneration and revascularization after RANTES-loaded MP local injection in mice hindlimb ischemia.